Takhrij and Syarah Hadith of Agrotechnology: Study of Disease-Fighting Black Cumin - Rika Rohmawati; Wahyudin Darmalaksana; Ida Yusidah (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the prophet muhammad (peace and blessings be upon him). About the black cumin. The methods used in this study are qualitative through the approach of the erstwhile and the shielding of agrotechnology. The results and discussions of this study are the popular black cumin plant of saw's time. Has many medicinal properties. The conclusion of this study is the throne and the prophet saw's throne. On black cumin as an herbal medicine in the time of god's prophet, not a modern-day cure for all sicknesses.